Generation of hydrogen-gas from aluminum dross - Meshram A.; Singh K.K. (My University, 2025)
Hydrogen presents itself as viable alternative to the conventional energy sources, as the combustion of hydrogen releases large amount of energy and the by-product is water vapour, a harmless gas. Aluminum dross is a waste product of aluminum melting/remelting units. The metal-water reaction between metallic content of aluminum dross and water is studied in this paper. Also various methods are discussed to enhance the production of hydrogen gas, in order to design an economic and sustainable process to treat aluminum dross. Copyright © European Metallurgical Conference, EMC 2017.All rights reserved.